Steuervergünstigungen in Deutschland - Alfred Boss (Kiel Institute for the World Economy (IfW), 2010)
Tax expenditures are granted for a variety of purposes in Germany. The paper presents data on the extent and the structure of the tax expenditures in the period 2003 to 2010. Tax expenditures were reduced somewhat in the period 2003–2006. However, they increased again thereafter.
Keywords: H24; H25; 330; Steuervergünstigungen; Subventionsabbau